2013
DOI: 10.1111/papr.12084
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pain Sensitivity on the Treatment Outcome of Transforaminal Epidural Steroid Injection in Patients with Lumbar Spinal Stenosis

Abstract: The aim of this study was to investigate the effect of individual pain sensitivity on the results of transforaminal epidural steroid injection (TFESI) for the patients with lumbar spinal stenosis (LSS). Seventy-seven patients with LSS were included in this study. Prospectively planned evaluations were performed twice consecutively before and 2 months after TFESI. These included a detailed medical history, a physical examination, and completion of a series of questionnaires, including pain sensitivity questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…[3][4][5] Abundant evidence has shown that biomedical factors cannot fully explain the chronic pain in musculoskeletal disorders. 6 , 7 Recently, it has been thought that psychosocial and environmental factors might have a potential causal relationship with chronic pain and the related disability.…”
mentioning
confidence: 99%
“…[3][4][5] Abundant evidence has shown that biomedical factors cannot fully explain the chronic pain in musculoskeletal disorders. 6 , 7 Recently, it has been thought that psychosocial and environmental factors might have a potential causal relationship with chronic pain and the related disability.…”
mentioning
confidence: 99%
“…38 Interviewees are asked to rate items of the PSQ that reflect imagined, typically painful stimuli. The PSQ has been used in different clinical and population-based settings 16,[22][23][24][25][26][27]37,39,43 and is available in several languages. 3,23,27,32,43,48 The PSQ showed good test-retest reliability in healthy volunteers 38 and clinical samples with degenerative spinal disease.…”
mentioning
confidence: 99%
“…The short‐term positive effectiveness of TFESI for controlling radicular pain following LSS has been well demonstrated in several previous studies 7,11–14 . However, the long‐term outcome of TFESI on LSS has been rarely studied.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, it can block the transmission of nociceptive signals through the nerve fibers 10 . The short‐term pain‐reducing effects of lumbar TFESI is well demonstrated 7,11–14 . However, little is known about the long‐term effect of lumbar TFESI for managing lumbar radicular pain due to LSS.…”
Section: Introductionmentioning
confidence: 99%